P327 Segmental colectomy for ulcerative colitis: a new paradigm? A multi-centric study in 72 patients. (25th January 2019) - Frontali, A; Panis, Y; Cohen, L; Bridoux, V; Myrelid, P; Sica, G; Poggioli, G; Espin, E; Beyer-Berjot, L; Laharie, D; Spinelli, A; Zerbib, P; et al.
Abstract: Background: The gold standard of surgery for ulcerative colitis (UC) is total coloproctectomy (TCP) with J-pouch. The only alternative is total colectomy (TC) with ileorectal anastomosis. There is no place for segmental colectomy (SC) due to the supposed high risk of postoperative colitis in the remnant colon. The aim of this study was to report a multi-centric experience of SC in UC patients to assess if SC can represent an alternative to TCP or TC. Methods: This was a retrospective multi-centric study from expert centres in Europe and US. All UC patients undergoing SC were included. Postoperative complications according to Clavien-Dindo's classification, long-term results and risk factors for postoperative colitis and reoperation for colitis on the remnant colon were assessed. Results: 72 patients (50 men (70%), with a mean age at diagnosis of UC of 46 ± 18 years and mean age at SC of 57 ± 17 years were included: sigmoidectomy ( n = 28), right colectomy ( n = 24), proctectomy ( n = 11) and left colectomy ( n = 9). Indications for surgery were: colonic cancer ( n = 27), sigmoid 'diverticulitis' ( n = 17), colonic stenosis ( n = 5), colonic dysplasia or polyps ( n = 8), and miscellaneous ( n = 15). Postoperative complications were observed in 17/72 patients (24%): classified Clavien-Dindo I-II in 7 (10%) and III or more in 10 (14%). Three patients died postoperatively (4%) due to respiratory ( n = 2) or hepatic ( n = 1) failure. 5/69 patients (7%) developed early flare of UC before 3 months postoperatively: 2 treated initially medically of whom 1 required completion TC and 3 with refractory colitis requiring either completion SC ( n = 1), completion TC ( n = 1) or TCP with definitive end ileostomy ( n = 1); 29/64 other patients (45%) developed flare of UC more than 3 months after SC after a median delay of 26 months. Among them, 12/29 (41%) underwent surgery (1 SC, 3TC and 8 TCP), after a median delay of 26 months after SC. After a median follow-up of 40 months, 24/69 patients (35%) were reoperated after a median delay after SC of 19 months: 22/24 (92%) underwent TC ( n = 9) or TCP ( n = 13) and 2/24 (8%) an additional SC. Reasons for redosurgery were: colitis ( n = 14; 20%), cancer ( n = 3) or dysplasia ( n = 3), colonic stenosis ( n = 1), and unknown reason ( n = 3). Endoscopic score before SC was Mayo II-III in 5/5 (100%) patients with early flare vs. 16/44 without (36%; p = 0.01) and in 9/12 (75%) patients with reoperation for colitis vs. 11/35 without (31%; p = 0.02). Conclusions: After segmental colectomy in UC patients, postoperative early colitis is rare (7%) with only 20% requiring reoperation for colitis during follow-up. Thus, in selected UC patients with no active colitis, segmental colectomy could represent a reasonable alternative to total coloproctectomy or total colectomy.